New Techniques and Methods of Data Collection - Azad, Bachchu Singh (AG Volumes, 2025)
Data is simply the information required to examine a research issue after a well-designed study. Data collection is essential because without the precise information obtained, research cannot be carried out. Review the many researchers’ studies on data gathering strategies and procedures in this page. It concluded that the selection of appropriate data collection methods is crucial for enhancing research quality and efficiency. Different techniques have their strengths and limitations depending on factors such as participant demographics and research objectives. The rise of online platforms has further expanded data collection possibilities, necessitating adherence to ethical guidelines. Utilizing advanced tools and software optimizes data management and analysis, leading to insightful outcomes. Combining various analytical techniques ensures comprehensive interpretation and evidence-based decision-making. The practical application of a minimum dataset aids in systematic data planning, while pre-collected routine data remains valuable for ongoing research efforts.